P Pengembangan Media Pembelajaran Pedom Cah dengan Pendekatan Kontekstual pada Materi Pecahan - Wiwin Purnama Sari; Lathifatul Khoiriyah; M Kemal Pasha; Lidya Desma Amanda; Siti Khoiriyah (Universitas Sarjanawiyata Tamansiswa, 2025)
Changes in education are one of the major impacts of the development of information technology. Technology has transformed the learning process from conventional to modern approaches. One innovation that can be applied is integrating learning media with technology. One such innovation is